Nanostructured Cu2O-based photocathode for artificial photosynthesis - Tan, Yong Ming (2015)
In recent years, development of sustainable energy has been playing an important role in creating an alternative to conventional energy sources amid the energy crisis. Hydrogen is considered as a potential clean energy source in replacing the fossil fuel and one of the sustainable ways to produce hydrogen is through water splitting by artificial photosynthesis. Among all the different approaches, photoelectrochemical cell has been proven to be very promising. Selection of candidates for photocathode used in water spitting process was studied in this project and it was done by ranking of some important factors of the materials such as position of band gap, absorption coefficient, stability, availability and others. Cu2O was chosen to be the material due to its suitable band gap position for redox reaction of water, availability, low cost and good absorption at visible spectrum. However, certain drawbacks still exist in cuprous oxide being photocathode in photoelectrochemical water splitting so further studies were carried out in order to improve the performance of Cu2O. The studies and works done on Cu2O photocathode include controlling the morphologies, improving the stabilities and enhancing the charge separation. Layered double hydroxides are a group of two-dimensional materials with general formula M(II)1-xM(III)x(OH)2(An-)x/n x yH2O. In this project, layered double hydroxides were discovered to have significant effect on the performance of photoelectrochemical water splitting if they are deposited on top of Cu2O photocathode. The enhancement is achieved by improvement of the charge transportation especially at low bias. This is due to electrocatalytic characteristic of NiFe LDH that drives the migration of electrons to the electrode surface. Furthermore, the stability of Cu2O photocathode is also improved after deposition of NiFe layered double hydroxides.